2013
DOI: 10.1080/00958972.2013.778987
|View full text |Cite
|
Sign up to set email alerts
|

Electroanalytical, kinetic, and mechanistic investigations of coordination-inspired electron transfer between Fe(II)/Cu(II)

Abstract: Herein, we report that the thermodynamic barrier for solution-phase electron transfer (ET) between Cu(II) and Fe(II) in aqueous acidic media can be overcome through the addition of 2,9-dimethyl-1,10-phenanthroline (Neocuproine [NC]) to the reaction mixture. A detailed discussion of the kinetic and mechanistic aspects of this coordination-inspired ET is presented. We attribute the observed change in the thermodynamic feasibility to the change in the reduction potential of Cu(II)-Cu(I) couple on its ligation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…The control experiment (Table , entry 18) proved that this reaction is not suitable in an inert atmosphere. Based on our experiments and the preceding literature, the plausible reaction mechanism was proposed and presented in Scheme . It is worth mentioning that the direct use of CuI is not a better choice in this reaction (Table , entry 21).…”
Section: Resultsmentioning
confidence: 99%
“…The control experiment (Table , entry 18) proved that this reaction is not suitable in an inert atmosphere. Based on our experiments and the preceding literature, the plausible reaction mechanism was proposed and presented in Scheme . It is worth mentioning that the direct use of CuI is not a better choice in this reaction (Table , entry 21).…”
Section: Resultsmentioning
confidence: 99%
“…It is a known fact that Cu(II) complexes prefer to exist as Jahn-Teller distorted octahedrons (though other configurations are known), while Cu(I) complexes usually exist as four-coordinate tetrahedra. 28,36 Complexation with Cu(II) requires DIDE to undergo some structural reorientations against the optimized (lowest energy) structure which makes complexation somewhat unfavourable as compared to Cu(I) wherein the four donor atoms persist with the same spatial arrangement. This preferential affinity for Cu(I) of DIDE hence results in an increase in the reduction potential of the Cu(II)/Cu(I) couple which is responsible for its observed potential to reduce the copper induced oxidative damage to BSA.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in the reduction reaction geometry transformation slows down the rate of electron transfer. Raashid and coauthors [21] reported the spectrophotometric study of kinetics and mechanism of NC assisted Fe(II)-Cu(II) process in which the absorbance time plot indicated electron transfer completion in ca 120-130 s [11]. The concentration effect on kinetic profile study justified the pseudo 2nd order kinetics with respect to the NC ligand and first order kinetics with respect to both Cu(II) and Fe(II).…”
Section: 3mentioning
confidence: 87%